Dinamika Perubahan Sosial dalam Pendidikan di SMK GKST di Poso - Sampe, Revina; Nuraedah; Idrus (Jurusan Pendidikan IPS, Fakultas Keguruan dan Ilmu Pendidikan Universitas Tadulako, 2022)
This paper aims to describe the history of the formation, development and dynamics of social change in education at SMK GKST in Poso. This type of descriptive qualitative research. The research subjects consisted of school principals. Data collection techniques in the form of observation, interviews and documentation. The data analysis used is data reduction, data presentation and conclusion drawing. The results showed that: In 1961 the Christian Education and College Foundation–Central Sulawesi Christian Church issued a Decree No. 14 /C.I – I.2 / 61 stipulates that since November 29, 1961, the High School Teacher (SGA) has been officially established which has started the teaching process since August 1, 1961. The development of the Poso GKST Vocational School can be seen from its physical development and the number of teaching staff and teachers. students and students who every year has increased. The relationship between the Poso GKST Vocational School and the surrounding community can be said to be good. Teachers and students who are at SMK GKST Poso have good social relations with the community around SMK GKST Poso. Many alumni of SMK GKST Poso have finished and have professions such as working in companies, members of the TNI military, entrepreneurs and several alumni who continue in higher education.